Commodity trade and finance - Tamvakis, Michael N. (Abingdon, Oxon : Informa Law, 2015)
'What affects the supply of oil? How important is the weather in determining grain prices? Why has the price of copper skyrocketed? This unique book analyses the economics of key commodity groups, including energy, agriculture and metals. It examines the supply/demand fundamentals of several major and minor commodities, physical characteristics, production and consumption patterns, trade flows and pricing mechanisms. It also explains the main tools used to hedge price risk, such as futures, options and swaps.This second edition contain has been fully revised and restructured, and contains 4 new chapters, including oil refining, electricity and price risk management for energy, metals and agricultural commoditiesThis book is an indispensable reference text for students, academics and those working in the commodity business'--
'This second edition contain has been fully revised and restructured, and contains 4 new chapters, including oil refining, electricity and price risk management for energy, metals and agricultural commodities'--
Includes bibliographical references and index.
Keywords: Primary commodities; Primary commodities -- Prices; International trade; Commodity exchanges